Hyper-local branding of Perak cuisine: a conceptual framework through Stuart Hall’s encoding/decoding model - Abdullah, Anwar Fikri; Sulaiman, Shahrunizam; Mhd Nor, Muhammad Nor Razin; Wan Muhammad Zulkifli, Wan Nurul Izzati (Universiti Teknologi MARA, Perak, 2025)
This conceptual paper examines the potential of hyper-local branding to preserve and promote Perak's culinary heritage through the lens of Stuart Hall’s Encoding/Decoding Model. Hyper-local branding foreground’s regional identity, cultural narratives, and authenticity in local cuisine, yet the growing influence of globalization, homogenization of taste, and the commodification of food culture pose significant threats to sustaining culinary distinctiveness. The problem addressed in this study is the lack of a systematic framework that connects semiotics, cultural identity, and branding in the Malaysian food context, particularly for under-represented cuisines such as those from Perak. While previous research has examined food tourism, authenticity, and cultural preservation, there remains a research gap in integrating communication theory—specifically Hall’s model—into the study of hyper-local branding practices. This paper contributes novelty by proposing a conceptual framework that reconceptualizes cuisine as a cultural text encoded by producers and decoded by diverse audiences. Methodologically, the paper adopts a conceptual and theoretical framework development approach, synthesizing insights from semiotics, gastronomy, and communication theory. By explicitly addressing the research gap in applying Hall’s Encoding/Decoding Model to hyper-local branding, the study develops propositions that can guide future empirical testing. The framework links literature on food heritage, flexible visual identity, and semiotics with audience reception studies, positioning it as a bridge between cultural theory and branding practice. By addressing the decoding of local cuisine branding, this paper advances the discussion beyond static notions of authenticity toward a more dynamic, dialogical understanding of branding as cultural negotiation. Implications extend to gastronomic tourism, heritage preservation, and branding practices, offering both theoretical and practical pathways for sustaining Perak’s culinary identity in the face of global cultural convergence.